2019
DOI: 10.12928/telkomnika.v17i4.11788
|View full text |Cite
|
Sign up to set email alerts
|

Neurocomputing fundamental climate analysis

Abstract: Rainfall is a natural phenomenon that needs to be studied more deeply and interesting to be analyzed. It involves numbers of human activities such as aviation, agriculture, fisheries, and also disaster risk reduction. Moreover, the characteristics of rainfall data follows seasonality, fluctuation, not normally distributed and it makes traditional time series challenging to use. Therefore, neurocomputing model can be used as an alternative to extraction information from rainfall data and give high performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The analysis of noisy ecological data [25], variables in ecology modelling [26], number of counts termites [27], community ecology and integrating species, traits, environmental, space [28], parameter in rainfall forecasting [29,30], global climate zone [31], local climate zone [32], environmental noise pollution [33], urban pollution [34,35], rainfall spatial temporal [36], flash flood hazard [37,38], landslide [39], earthquake damage detection using curvilinear features [40], earthquake classifiers using stochastic reconstruction [41] and tsunami [42] Health Future genetic association studies of colorectal cancer [11], Aortic Anatomy on Endovascular Aneurysm Repair (EVAR) [43], colorectal cancer cases phenotype [10], identify a wide range of predictors that could enhance prediabetes prediction and clinical decision-making [44], the classification of diabetes mellitus [45], type 2 diabetes within 2 years in an obese, hypertensive population [46], the principal purpose of coronary illness [47], heart disease [48], cardiovascular disease [49], ovarian cancer patients [50], gene expression RNA-Seq data [51,52], adjuvant chemotherapy effectiveness assessment in non-small cell lung cancer [53], and Alzheimer's disease [54] Finance Mineral prospect [12], Industrial recommendation system [13], financial crisis [55], industrial coal mine [56], poverty classification [57], spatiote...…”
Section: Subject Descriptionmentioning
confidence: 99%
“…The analysis of noisy ecological data [25], variables in ecology modelling [26], number of counts termites [27], community ecology and integrating species, traits, environmental, space [28], parameter in rainfall forecasting [29,30], global climate zone [31], local climate zone [32], environmental noise pollution [33], urban pollution [34,35], rainfall spatial temporal [36], flash flood hazard [37,38], landslide [39], earthquake damage detection using curvilinear features [40], earthquake classifiers using stochastic reconstruction [41] and tsunami [42] Health Future genetic association studies of colorectal cancer [11], Aortic Anatomy on Endovascular Aneurysm Repair (EVAR) [43], colorectal cancer cases phenotype [10], identify a wide range of predictors that could enhance prediabetes prediction and clinical decision-making [44], the classification of diabetes mellitus [45], type 2 diabetes within 2 years in an obese, hypertensive population [46], the principal purpose of coronary illness [47], heart disease [48], cardiovascular disease [49], ovarian cancer patients [50], gene expression RNA-Seq data [51,52], adjuvant chemotherapy effectiveness assessment in non-small cell lung cancer [53], and Alzheimer's disease [54] Finance Mineral prospect [12], Industrial recommendation system [13], financial crisis [55], industrial coal mine [56], poverty classification [57], spatiote...…”
Section: Subject Descriptionmentioning
confidence: 99%
“…In order to respond, in the last stage of the recovery process, the primary objective is to rebuild as well as stabilize the system so that it recovers immediately, as it would before the disaster recovers or improves for better transformation. Successful adaptation strategies will greatly reduce the likelihood of disasters [36]. There are three major stages of disaster risk mitigation adaptation, including the predisaster, disaster and post-disaster stages [37], [38]…”
Section: A Vulnerability Index Towards Natural Hazard Non-natural Hmentioning
confidence: 99%
“…The probability vector of steady-state π is an Eigenvector determined by Eigenvalue λ so that π must fulfil in equation (14).…”
Section: Vector Autoregressivementioning
confidence: 99%
“…Neural Network [13] is a nonparametric model that can be used for modelling time series data that does not require various residual assumptions. Several studies have found that this model produces better predictive accuracy than parametric models [14]. Beside of time dimension, data can also have a space dimension known as space-time data [15].…”
Section: Introductionmentioning
confidence: 99%